Patient safety culture, missed Nursing care and its reasons in Obstetrics - Silvana Cruz da Silva; Bruna Xavier Morais; Oclaris Lopes Munhoz; Juliana Dal Ongaro; Janete de Souza Urbanetto; Tânia Solange Bosi de Souza Magnago (Universidade de São Paulo, 2021)
Objective: to assess the correlations between the patient safety culture, the missed Nursing care, and the reasons for the omission in the obstetric area. Method: a cross-sectional study, conducted in 2019, with 62 Nursing professionals working in the obstetric area of a teaching hospital in southern Brazil. The MISSCARE-Brasil and Hospital Survey on Patient Safety Culture instruments were used. The data were analyzed using descriptive statistics, means comparison test and Spearman correlation. Results: the overall mean of positive answers for the safety culture was 34.9 (± 17.4). The care of assessing the vital signs and monitoring capillary blood glucose were the most prioritized, with airway aspiration and oral hygiene being the most overlooked. The main reasons for the omissions refer to labor resources and to inadequate staffing. A significant and inversely proportional correlation was found between the patient safety culture and overlooked nursing care (r=-0.393). Conclusion: the safety culture of the obstetric area was assessed as fragile by the Nursing professionals. The more the safety culture is strengthened and the greater investment in labor and human resources, the less care is overlooked.